ANALISIS PENYAJIAN LAPORAN KEUANGAN PADA PT. GARUDA SAKTI SENDAWAR - Umi Kulsum, Abdillah Fauzi, Elfreda Aplonia Lau (EKONOMIA, 2020)
The formulation of this research problem is whether the presentation of financial statements at PT. Garuda Sakti Sendawar has been in accordance with the provisions of presentation of financial statements SAK ETAP Year 2016. This study aims to know and present the financial statements at PT. Garuda Sakti Sendawar based on SAK ETAP Year 2016. The basic theory used in this study is financial accounting that focuses on the presentation of financial statements based on the financial accounting standards of entities without public accountability in 2016. To analyze the authors use the formula Dean J. Champion. The hypothesis of this study is the presentation of financial statements at PT. Garuda Sakti Sendawar Year 2014, 2015 and 2016 not in accordance with SAK ETAP Year 2016.The analytical tool used is the presentation of financial statements according to Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) Year 2016. The results of presentation of financial statements at PT. Garuda Sakti Sendawar 2014, 2015 and 2016 are not suitable according to SAK ETAP Year 2016 with a percentage range of 12.5%, so the hypothesis of this study is accepted.